2022
DOI: 10.7759/cureus.25919
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D Levels and Glycemic Control Among Adult Diabetic Patients in Riyadh, Saudi Arabia

Abstract: Background: Diabetes is one of the most common diseases worldwide. It can cause serious complications, such as cardiovascular events, end-stage renal disease, and blindness if not controlled. Vitamin D is believed to play an essential role in glucose metabolism and insulin resistance. However, few studies have been conducted in Saudi Arabia to confirm or reject this hypothesis. Thus, this study explored the relationship between vitamin D levels and glycemic control in a Saudi diabetic population.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In Table 3, vitamin D levels>50ng/ml correlate with better glycemic control than patients with a vitamin D level of 30-50ng/ml (P-value<0.01). Different studies from various regions have investigated the effectiveness of vitamin D supplement therapy on glycemic control and level of HbA1c in type 1 diabetic patients and almost all of them indicated that vitamin D could improve glucometabolic status [41,42] and mean level of vitamin D was higher in the good glycemic group (70.96 ±22.66 ng/ml) than in the poor glycemic group (54.81±19.98ng/ml) [43]. A therapeutic dose of 50000IU/week can be given safely for 4) or other side effects as tolerable upper limit of daily dose of vitamin D in children up to 10000 IU/day [44].…”
Section: Discussionmentioning
confidence: 99%
“…In Table 3, vitamin D levels>50ng/ml correlate with better glycemic control than patients with a vitamin D level of 30-50ng/ml (P-value<0.01). Different studies from various regions have investigated the effectiveness of vitamin D supplement therapy on glycemic control and level of HbA1c in type 1 diabetic patients and almost all of them indicated that vitamin D could improve glucometabolic status [41,42] and mean level of vitamin D was higher in the good glycemic group (70.96 ±22.66 ng/ml) than in the poor glycemic group (54.81±19.98ng/ml) [43]. A therapeutic dose of 50000IU/week can be given safely for 4) or other side effects as tolerable upper limit of daily dose of vitamin D in children up to 10000 IU/day [44].…”
Section: Discussionmentioning
confidence: 99%